Linked Stories, Connected Lives: The Lucky Ones as Short Story Cycle - Elke D’HOKER (E-REA)
This essay considers the thematic repercussions of the peculiar narrative and generic structure of The Lucky Ones as a collection of linked short stories. The form of the short story cycle allows Cusk to stage a variety of perspectives on parenthood and family life within one book. Moreover, the tension between unity and fragmentation, which is characteristic of the form, serves to highlight the tension between individualism and connection or community in The Lucky Ones. Even though the protagonists remain bound within their own lives, families and stories they can be seen to yearn for connection and communion in the epiphanic moments that mark the singular stories. In the final part of the paper, I consider Cusk’s representation of contemporary community as a loose network of relations within the context of recent approaches to community in social theory and philosophy.